183k views
4 votes
Sketch the graph of y = - 2f(x-3)+1 given the current function.

Sketch the graph of y = - 2f(x-3)+1 given the current function.-example-1
User Asynts
by
4.3k points

1 Answer

1 vote

ANSWER

Step-by-step explanation

There are many transformation of function f(x)

The first transformation is an horizontal translation 3 units to the right: f(x - 3)

The next transformation is a dilation by a factor of 2: 2f(x-3)

The next one is a reflection over the x-axis: -2f(x-3):

And finally there's a translation 1 unit up: -2f(x-3) + 1

Sketch the graph of y = - 2f(x-3)+1 given the current function.-example-1
Sketch the graph of y = - 2f(x-3)+1 given the current function.-example-2
Sketch the graph of y = - 2f(x-3)+1 given the current function.-example-3
Sketch the graph of y = - 2f(x-3)+1 given the current function.-example-4
Sketch the graph of y = - 2f(x-3)+1 given the current function.-example-5
User IndigoFire
by
4.6k points